Single cell transcriptomics reveals reduced stress response in stem cells manipulated using localized electric fields. (April 2023) - Mukherjee, Prithvijit; Peng, Chian-Yu; McGuire, Tammy; Hwang, Jin Wook; Puritz, Connor H.; Pathak, Nibir; Patino, Cesar A.; Braun, Rosemary; Kessler, John A.; Espinosa, Horacio D.
Abstract: Membrane disruption using Bulk Electroporation (BEP) is a widely used non-viral method for delivering biomolecules into cells. Recently, its microfluidic counterpart, Localized Electroporation (LEP), has been successfully used for several applications ranging from reprogramming and engineering cells for therapeutic purposes to non-destructive sampling from live cells for temporal analysis. However, the side effects of these processes on gene expression, that can affect the physiology of sensitive stem cells are not well understood. Here, we use single cell RNA sequencing (scRNA-seq) to investigate the effects of BEP and LEP on murine neural stem cell (NSC) gene expression. Our results indicate that unlike BEP, LEP does not lead to extensive cell death or activation of cell stress response pathways that may affect their long-term physiology. Additionally, our demonstrations show that LEP is suitable for multi-day delivery protocols as it enables better preservation of cell viability and integrity as compared to BEP. Graphical abstract: Image 1 Highlights: Localized electroporation emerges as an efficient and precise alternative to bulk electroporation for cell transfection. Adverse effects of electroporation on stem cell physiology are poorly understood. Bulk electroporation induces extensive stress response gene expression in stem cells. Minimal stress in localized electroporation is beneficial for multi-day transfections.